Common platform integration for complex relational database management - Dubey, Santosh (2016)
The Complex Database Integration Principle is a concept that proliferates the adoption of a heterogeneous distributed or multi data-driven systems approach with the mediation of a common platform that allows view compatibility in complexity. This idea attempts to simplify, make complete and improve precision of conceptual process cycles in complex software, usually with global queries or translators, to ensure assiduity in cyclic practices to an extent where formed construct becomes amenable for relational databases. This integration is expected to encompass factors for general object-oriented development outcomes leading to Knowledge Engineering process cycles with the available integrity. This study explores the integration of seemingly autonomous and heterogeneous relational database technologies to derive reliability from a research prototype project, the Multi-Platform Relational Database Editor (MRDE) that was developed to address the need for a production quality multi-database integration driven approach for simplification of complex heterogeneous relational database management principles.